Performance of elite castor (Ricinus communis L.) hybrids and varieties under rainfed Alfisols: PERFORMANCE OF ELITE CASTOR HYBRIDS AND VARIETIES UNDER RAINFED ALFISOLS - R MOHAN KUMAR; YAMANURA; B BORAIAH (Journal of Oilseeds Research, 2021)
A field experiment was conducted during the rainy (kharif) seasons of 2018 and 2019 at Zonal Agricultural Research Station, University of Agricultural Sciences, Bangalore to study the per se performance, productivity and profitability of seven elite castor hybrids and varieties. Treatments comprised five hybrids (GCH-8, DCH-177 DCH-519, GCH-7, GCH-4) and two varieties (48-1, DCS-107). Based on the pooled analysis, castor hybrids (GCG-8, DCH-177 and DCH-519) showed significantly higher total dry matter production (TDMP) on account of significant superiority in crop growth rate (CGR), relative growth rate (RGR) and absolute growth rate (AGR). Nevertheless, the performance of genotypes in this study was not a true reflection of their growth attributes. Therefore, castor genotypes did not show consistency for seed yield over the years of their evaluation. It was mainly due to their differential reaction to incidence of gray mold. During 2018 significantly higher grain yield (2369 kg/ha), oil yield (1152 kg/ha), gross return (` 1,23,188/ha), net return (` 99,809/ha) and benefit: cost ratio (3.95) was recorded in GCH-8. Whereas, during 2019, 48-1 recorded significantly higher grain yield (1270 kg/ha), oil yield (602 kg/ha), gross return (` 66,040/ha), net return (` 36,897/ha) and benefit: cost ratio (2.27). Based on the pooled analysis, castor hybrid GCH-8 (1777 kg/ha) recorded significantly higher yield and closelyfollowed by castor variety 48-1 (1476 kg/ha) and DCS-107 (1444 kg/ha).